HUMAN RIGHTS LAW ANALYSIS OF AFGHANISTAN ASYLUM SEEKERS IN INDONESIA - Setya Putra, Royce Wijaya; Widyawati, Anis; Sri Utari, Indah; Henri Pelupessi, Ignatius (Jurnal Meta-Yuridis, 2025)
The prolonged social conflict in Afghanistan has caused its citizens to flee to various countries around the world. Asylum seekers from this country located in Central and South Asia often face challenges in legal protection, especially in asylum-receiving countries such as Indonesia. Although it does not have an official policy regarding refugees, Indonesia is one of the transit destinations for asylum seekers, including those who are refugees from the conflict in Afghanistan. The study aims to analyze the protection, challenges, and mechanisms of legal protection for asylum seekers from Afghanistan in Indonesia. A qualitative approach is used in the study that relies on literature reviews, such as books, scientific articles, institutional reports, and documents related to the protection of asylum seekers. Indonesia is a member of international legal instruments, such as the 1951 Refugee Convention, but does not yet have a clear national legal framework to protect the rights of asylum seekers. In Indonesia, asylum seekers from Afghanistan face legal uncertainty, limited access to basic services, and the potential risk of deportation to an unsafe country of origin